2009
DOI: 10.1116/1.3237145
|View full text |Cite
|
Sign up to set email alerts
|

Reversible shape changes of the end facet on Schottky electron emitters

Abstract: The Schottky electron source is predominant in today's focused electron-beam equipment, but its properties are still not fully understood. Generally, its performance is predicted, assuming its tip end geometry is known and stable. In this work, it is shown that the size of the end facet ͑slowly͒ shrinks upon reduction in the extraction voltage and ͑more rapidly͒ grows upon restoration of the original voltage. Furthermore, the shape of the end facet could be made to change from more circular to octagonal or mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Previous studies [1][2][3][4][5][6][7] have shown that the SE source reaches a quasi equilibrium state resulting in one of four polyhedral shapes that involve various combinations of enlargement or contraction of the four {112} and {110} crystal planes adjacent to the central (100) facet. The SE source in this context is a point electron source consisting of a W(100) oriented single crystal with a ZrO 2 over layer and operated at 1800 K. In order to obtain the optimum source performance for a given electron optical application, it is necessary to know how the emission parameters vary with emitter geometry and evolve over time.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [1][2][3][4][5][6][7] have shown that the SE source reaches a quasi equilibrium state resulting in one of four polyhedral shapes that involve various combinations of enlargement or contraction of the four {112} and {110} crystal planes adjacent to the central (100) facet. The SE source in this context is a point electron source consisting of a W(100) oriented single crystal with a ZrO 2 over layer and operated at 1800 K. In order to obtain the optimum source performance for a given electron optical application, it is necessary to know how the emission parameters vary with emitter geometry and evolve over time.…”
Section: Introductionmentioning
confidence: 99%